Increasing the productivity of tropical farming systems - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Raising and sustaining the productivity of smallholder farming systems in the tropics by Willem C Beets 1990 approx 800pp, 300 illustrations price US$65 AgBe Publishing PO Box 9125 1800 GC Alkmaar THE NETHERLANDS